Interaction of MRI field gradients with the human body - Glover, Paul (IOP, 2009)
In this review, the effects of low-frequency electromagnetic fields encountered specifically during magnetic resonance imaging (MRI) are examined. The primary biological effect at frequencies of between 100 and 5000 Hz (typical of MRI magnetic field gradient switching) is peripheral nerve stimulation, the result of which can be a mild tingling and muscle twitching to a sensation of pain. The models for nerve stimulation and how they are related to the rate of change of magnetic field are examined. The experimental measurements, and analytic and computational modelling work in this area are reviewed. The review concludes with a discussion of current regulation in this area and current practice as both are applied to MRI.